Assessment of the Microclimatic Effects of Vegetation on the Mitigation of Urban Heat Island: Park in the City of Torreon, Mexico - Flores-De la O., Jesthly Leticia (2018)
The magnitude of the impacts caused by the climate variation over the cities will depend on their capacity for resilience. The literature about this issue identifies the urban green areas and the environmental services as a strategy to mitigate the urban heat island (UHI), a phenomenon of urban microclimate that has an impact on air quality, water, and energy demand: central themes in urban sustainability. Diverse studies refer to the consolidation of urban green areas as a strategy to mitigate climate risks; at the same time, these studies recognize the need of evaluating the environmental benefits, mainly in arid zones. This work explores, through the microclimatic analysis, the performance of the urban park of a greater surface in the city as a thermal sink. The analysis was conducted in two stages. The first one intended to classify the different environments inside the park; later, in the second stage, these environments were measured as microclimates using transects with HOBO data logger devices. In addition to demonstrating the convenience of the method, the results contribute to the evaluation of benefits of the green areas as thermal sink, and with this, to lay the foundations for the establishment of an urban planning policy aimed at mitigating the UHI in the city, contributing to the process of adaptation to climate change in cities with arid climate.